Characterization of Pseudomonas capsici strains from pepper and tomato - Zhao, Mei; Gitaitis, Ron; Dutta, Bhabesh (Frontiers in Microbiology, 2023)
Disease outbreaks of bacterial leaf spot and blight of pepper and tomato often occur in production systems worldwide. In some cases, the outbreaks are caused by novel bacterial species. In this manuscript we aimed to characterize strains belonging to novel Pseudomonas species that are responsible for outbreaks in pepper and tomato both in transplant houses and in production fields in Georgia, USA and also determined the genetic relatedness based on whole-genome sequencing with Pseudomonas strains from other sources. Phylogenomic analyses and whole genome sequence indices demonstrated that the pepper and tomato strains belonged to P. capsici. The whole-genome comparison revealed that 13 Pseudomonas strains from diverse isolation sources that were curated in NCBI were indeed P. capsici indicating a potential wide-host range for this bacterial species. Our greenhouse based host-range assay also indicated that P. capsici strains were pathogenic on pepper, tomato, eggplant, cabbage, lettuce, and watermelon corroborating a wide-host-range. A phylogenetic tree inferred from the whole genome sequence showed that the P. capsici strains from Georgia were genetically diverse, and were closely related to tomato P. capsici strains from Florida. Genomic presence of traditional bacterial virulence factors in P. capsici strains was also determined. P. capsici strains encode one set of type I secretion system, two sets of type II secretion systems, one set of type III secretion system, two sets of type V secretion systems, three sets of type VI secretion systems, and various secondary metabolite gene clusters including lipopeptides. In in-vitro assays, it was demonstrated that six out of seven P. capsici strains (pepper and tomato strains from Georgia) were not sensitive to 0.8 mM CuSO4. When the genomes of copper-tolerant strains were compared with the copper-sensitive strains, it was observed that the former strains encode a cluster of genes related to copper tolerance, which were absent in the genomes of copper-sensitive strains. Considering the ability of P. capsici strains to infect a range of vegetable hosts and possession of a wide range of bacterial virulence factors, secondary metabolites, and copper-tolerance genes, we envision that the management of this pathogen might potentially be a challenge.